“Ex Marte se procreatum” – Did the Roman Emperor Galerius Make Mars his Personal Protective Deitie? - Bralewski, Sławomir (Studia Ceranea, 2023)
Lactantius referred in his work On the Deaths of the Persecutors (De mortibus persecutorum) to a great victory which Caesar Galerius won over the Persians. From then on, he demanded for himself the title of Augustus and, we are made to believe, insisted upon being called a son of Mars as second Romulus. Did he thus deviate from the truth? Or, on the contrary, did Galerius render Mars his divine patron and does Lactantius’ account remain in agreement with other sources and reflect the true course of events. The aim in this article is to resolve this issue. It thus seems that as a result of the triumph over the Persians, which he was believed to owe to Mars, Galerius gained a new position already under the first tetrarchy, which Lactantius testifies to in his work On the Deaths of the Persecutors. It is thus clear that Lactantius’s testimony according to which Galerius recognized Mars as his divine patron is credible and remains in agreement both with a number of other sources and with the true course of events.